O-GlcNAcylation and the Metabolic Shift in High-Proliferating Cells: All the Evidence Suggests that Sugars Dictate the Flux of Lipid Biogenesis in Tumor Processes - Baldini, Steffi F.; Lefebvre, Tony (Frontiers in Oncology, 2016)
Cancers cells are characterized by their high capability to proliferate. This imposes an accelerated biosynthesis of membrane compounds to respond to the need for increasing the membrane surface of dividing cells and remodeling the structure of lipid microdomains. Recently, attention has been paid to the up-regulation of O-GlcNAcylation processes observed in cancer cells. Although O-GlcNAcylation of lipogenic transcriptional regulators is described in the literature (e.g. FXR, LXR, ChREBP) little is known about the regulation of the enzymes that drive lipogenesis: ACC (Acetyl Co-enzyme A carboxylase) and FAS (Fatty Acid Synthase). The expression and catalytic activity of both FAS and OGT (O-GlcNAc transferase) are high in cancer cells but the reciprocal regulation of the two enzymes remains unexplored. In this perspective, we collected data linking FAS and OGT and, in so doing, pave the way for the exploration of the intricate functions of these two actors that play a central role in tumor growth.